QUANTIFYING SRH RECOMBINATION IN GAAS PIN SOLAR CELLS - Choudhury, Aditya N. Roy (International Journal of Engineering Science Technologies, 2025)
Charge recombination is known to decrease a solar cell’s efficiency. SRH recombination, which is always present in a solar cell, is, thus, a candidate about which knowledge must be extracted. SRH recombination affects the dark current, the photocurrent and, thus, the total current of a solar cell. To find the SRH recombination times, elaborate numerical simulations must be done and the experimental solar cell data must be curve fitted to the simulation results. This is a lengthy and detailed procedure. In this work, a simple and short method is proposed. A GaAs PIN solar cell is simulated and its photocurrent’s slope (vs. voltage) is seen to show a peak which decreases with decreasing recombination times. A plot is given, from which the recombination time can be easily read by knowing the photocurrent’s slope’s peak value. This peak value can be easily found from the solar cell’s experimentally measured data.